Production and characterization of kombucha-like beverage by cocoa (Theobroma cacao) by-product as raw material - Lívia de Matos Santos; Mariana Nougalli Roselino; Janaína de Carvalho Alves; Suelen Neris Almeida Viana; Elis dos Reis Requião; Jéssica Maria Rio Branco dos Santos Ferro; Carolina Oliveira de Souza; Camila Duarte Ferreira Ribeiro (Future Foods)
Cocoa is one of the most consumed products globally. However, only approximately 20 % of cocoa is utilized, leading to a search for alternatives and ways to utilize the by-products, which represent approximately 80 % of the fruit and have nutritional potential. Therefore, this work aimed to produce and characterize a beverage similar to kombucha using cocoa bean shell (CBS) at different concentrations (0.7 %, 1.5 %, and 2.3 %). The fermented beverage was analyzed for alcohol content, antioxidant activity, structure of symbiotic cultures of bacteria and yeast using scanning electron microscopy (SEM), as well as pH, soluble solids, titratable acidity, color parameters, and total phenolic compounds (TPCs) after 0, 3, 6, 9, and 12 d of storage at 2.7 ± 0.06 °C. The results showed the absence of alcohol content, antioxidant activity in all the analyzed formulations, and dense, interconnected structures in the SEM analysis of symbiotic cultures developed during fermentation. Variations were identified in the analyzed parameters, namely pH (from 3.58 ± 0.01 to 3.61 ± 0.02), soluble solids (ºBrix) (from 7.03 ± 0.06 to 7.13 ± 0.06), and titratable acidity (g of acetic acid/100 ml) (from 0.29 ± 0.00 to 0.31 ± 0.01). Interestingly, concerning color parameter, a significant influence of CBS content on luminosity parameter was evidenced (ranging from 90.25 ± 0.01 to 92.45 ± 0.06) and on reddish hue (with variation from 2.01 ± 0.01 to 1.53 ± 0.07), in addition to variation in TPC content (ranging from 2.33 ± 0.00 to 1.73 ± 0.00). For the sensory profile, the average acceptance rate of the three formulations was 68.6 %, and the average purchase intention ranged 2.98–3.20. High-throughput sequencing revealed that the primary bacterial genera were Komagataeibacter, Acetobacter, and Gluconacetobacter, and the predominant genera of yeasts were Brettanomyces and Pichia. In conclusion, CBS has significant potential for the development of innovative food products.